Pengaruh Faktor Psikologis terhadap Pengambilan Keputusan Investasi Generasi Z di Kota Denpasar: Pendekatan Kualitatif Behavioral Finance” - Gede Widiadnyana Pasek; I Putu Agus Adnyana; Gede Widiastina (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2026)
The development of digital technology has catalyzed a growing interest in investment among Generation Z, particularly in Denpasar. Easy access to various digital investment platforms, social media, and financial information has rendered the younger generation increasingly active in investing. However, in practice, investment decision-making is not always rational; rather, it is influenced by various psychological factors such as overconfidence, herding behavior, fear of loss, and investor sentiment. This phenomenon makes the investment behavior of Generation Z an intriguing subject to examine through a behavioral finance approach. This study aims to understand the influence of psychological factors on investment decision-making among Generation Z in Denpasar. Utilizing a qualitative approach, this study adopts a phenomenological research design. Informants were selected using a purposive sampling technique, with the criteria being Generation Z individuals who actively invest through digital platforms. Data collection was conducted through in-depth interviews, observation, and documentation. The data analysis technique followed the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing/verification. Data validity was ensured through source and technique triangulation. The results indicate that psychological factors exert a significant influence on the investment decision-making of Generation Z. Overconfidence tends to make young investors overly confident in their analytical skills, while herding behavior emerges due to the influence of social media, investment communities, and the fear of missing out (FOMO) phenomenon.